Shedding light on the role of bHLH transcription factors in Arabidopsis thaliana male reproductive development - Robson, Jordan Kirsty (2021)
Development of viable pollen in the anther locule is crucial for plant reproduction, and relies upon secretion of proteins, lipids, polysaccharides and other essential molecules from the surrounding tapetum tissue. Tapetum development in Arabidopsis thaliana is regulated by a number of genes including the basic Helix Loop Helix (bHLH) transcription factors DYSFUNCTIONAL TAPETUM (DYT1) and ABORTED MICROSPORES (AMS), which interact competitively with bHLH010, bHLH089 and bHLH091 to regulate downstream targets involved in synthesis and secretion of pollen wall components. Disruption of genes within the tapetum development pathway leads to male sterility and previous research has shown that ams, dyt1 and bhlh089 bhlh010 amiR-bHLH091 knockout mutants are completely male sterile, whereas the single and double bhlh010, -089 and -091 mutants are mostly fertile due to a high level of functional redundancy.